Pernikahan Beda Agama di Indonesia - Nur Adila Nasution; Syaima Desinta Maharani; Muhammad Yusuf; Fauzianor (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Marriage is a sacred institution that serves as the primary foundation for the formation of families and social order. In the context of Indonesia, which is rich in cultural and religious diversity, the issue of interfaith marriage has given rise to a long discourse on the relationship between religious principles, legal provisions, and human rights values. This study aims to conceptually examine the legal status, legitimacy, and socio-legal implications of the practice of interfaith marriage from the perspective of Islamic law and Indonesian positive law. By applying library research methods and a qualitative descriptive approach, this study analyzes various literature sources, laws and regulations, and the views of scholars from various schools of thought. The results show that, according to both Islamic law and Law Number 1 of 1974, interfaith marriage is not legally valid because it contradicts the provision that marriage must be conducted in accordance with the teachings of each religion. The Indonesian Ulema Council (MUI) fatwa also affirms its prohibition, including for Muslim men marrying women from the People of the Book. However, there is a legal loophole that allows for the registration of interfaith marriages through a district court ruling. In conclusion, the practice of interfaith marriage in Indonesia faces a dilemma between individual freedom and adherence to religious norms. Therefore, clear regulations are needed to avoid future legal dualism.